An ultra-folded lithium ion battery electrode material, a preparation method thereof, and an ultra-folded full battery
Patent Information
- Application Number
- CN202411198057.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-29
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2044-08-29
AI Technical Summary
传统的本征导电材料,不论金属、导电高分子还是碳材料,由于刚性短程的化学键限制,导致其不能够经受住大量次数的真折叠
[0016]根据本发明实施例提供的一种超折叠锂离子电池电极材料、其制备方法以及超折叠全电池,因为超折叠锂离子电池电极材料的制备方法中,首先将碳纳米管和LiFePO4颗粒分散在N,N-二甲基甲酰胺溶液中,依次超声、搅拌获得均匀的悬浊液,再将聚丙烯腈加入悬浊液中,通过搅拌促进聚丙烯的溶解得到高分子混合凝胶,然后将高分子混合凝胶装入注射器中进行静电纺丝制备高分子膜前驱体,再将高分子膜前驱体在管式炉中进行预碳化处理,得到预碳化样品,最后对预碳化样品进行碳化处理,得到超折叠锂离子电池电极材料。
Smart Images

Figure CN119069673B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of flexible energy storage, specifically relating to an ultrafoldable lithium-ion battery electrode material, its preparation method, and an ultrafoldable full battery. Background Technology
[0002] As people's demands for portability and functionality in electronic products increase, the foldability of flexible electronics is becoming increasingly important. However, the development of foldable electronic products is currently in its early stages. Although some foldable devices and even products have emerged, they do not achieve a true 180-degree fold with both sides close together. Currently available foldable smartphones fold using a rotating axis and cannot be arbitrarily deformed or reduced in size. Energy storage devices, the cornerstone of next-generation foldable electronic products, are still largely rigid structures, which significantly hinders the development of foldable electronics. Traditional intrinsically conductive materials, whether metals, conductive polymers, or carbon materials, cannot withstand a large number of true folds due to the rigidity and short-range chemical bond limitations. Furthermore, existing electrochemically active materials typically have higher rigidity; when combined with traditional flexible substrates, this further reduces the overall flexibility, making true folding even more difficult. Consequently, the assembled devices fall far short of the requirements for true folding.
[0003] Therefore, the preparation of an electrode material that satisfies superfolding performance while also possessing high electrical conductivity and a full cell has become an urgent problem to be solved. Summary of the Invention
[0004] This invention is made to solve the above-mentioned problems, and aims to provide a superfoldable lithium-ion battery electrode material, its preparation method, and a superfoldable full battery.
[0005] This invention provides a method for preparing a superfoldable lithium-ion battery electrode material, characterized by utilizing electrospinning combined with gradient temperature carbonization technology. Specifically, the method includes the following steps: S10, dispersing carbon nanotubes and LiFePO4 particles in an N,N-dimethylformamide solution, followed by ultrasonication and stirring to obtain a suspension; S20, adding polyacrylonitrile to the suspension, and promoting the dissolution of polyacrylonitrile by stirring to obtain a polymeric mixed gel; S30, loading the polymeric mixed gel into a syringe for electrospinning to prepare a polymeric film precursor; S40, pre-carbonizing the polymeric film precursor in a tube furnace to obtain a pre-carbonized sample; S50, carbonizing the pre-carbonized sample to obtain the superfoldable lithium-ion battery electrode material.
[0006] The method for preparing the superfoldable lithium-ion battery electrode material provided by the present invention may also have the following characteristics: in step S10, the amount of N,N-dimethylformamide solution is 5-10 mL, the amount of carbon nanotubes is 0.01-0.7 g, the size of LiFePO4 particles is 10 nm-300 nm, the amount of LiFePO4 is 0.01-0.6 g, the ultrasonic time is 1 h-8 h, and the stirring time is 1 h-8 h.
[0007] The method for preparing the superfoldable lithium-ion battery electrode material provided by the present invention may also have the following characteristics: in step S20, the amount of polyacrylonitrile used is 1.0-1.6g, the stirring time is 6h-48h, and in step S30, the conditions for electrospinning are: the voltage at the syringe needle connection end is set to 12-16kV, the voltage at the receiving end of the spun product is set to -2kV, the pushing speed is set to 0.01-0.02mL / min, the receiving distance is set to 18cm, and the needle pushing amount is 2mL / h.
[0008] The method for preparing the superfoldable lithium-ion battery electrode material provided by the present invention may also have the following features, wherein in step S40, the pre-carbonization process is as follows: the temperature is raised to 250-300℃ in an air atmosphere at a heating rate of 0.5-5℃ / min, and kept at 250-300℃ for 2 hours, and then naturally cooled to room temperature.
[0009] The method for preparing the superfoldable lithium-ion battery electrode material provided by the present invention may also have the following characteristics: the superfoldable lithium-ion battery electrode material is a superfoldable positive electrode material, and the carbonization process in step S50 is as follows: the temperature is raised to 250-300℃ at a heating rate of 2-5℃ / min under a nitrogen atmosphere and held for 1 hour, and then raised to 650-750℃ at a heating rate of 0.5-1.5℃ / min and held for 2 hours.
[0010] The method for preparing the superfoldable lithium-ion battery electrode material provided by the present invention may also have the following characteristics: the superfoldable lithium-ion battery electrode material is a superfoldable negative electrode material, and the carbonization process in step S50 is as follows: the temperature is raised to 250-300℃ at a heating rate of 2-5℃ / min under a nitrogen atmosphere and held for 1h, and then raised to 760-850℃ at a heating rate of 0.5-1.5℃ / min and held for 2h.
[0011] This invention provides a superfoldable lithium-ion battery electrode material, characterized by being prepared using the preparation method of the superfoldable lithium-ion battery electrode material provided by this invention.
[0012] This invention provides a superfoldable full battery, characterized by containing the superfoldable lithium-ion battery electrode material provided by this invention.
[0013] The superfold full battery provided by the present invention may also have the following characteristics, wherein it includes a superfold positive electrode material prepared by the preparation method of the superfold lithium-ion battery electrode material provided by the present invention and a superfold negative electrode material prepared by the preparation method of the superfold lithium-ion battery electrode material provided by the present invention.
[0014] The superfoldable full battery provided by this invention also has the following features, specifically including the following steps: First, take two pieces each of superfoldable positive electrode material and superfoldable negative electrode material, immerse them in a 1% lithium naphthalene solution for pre-lithiation treatment, and obtain lithiated superfoldable positive electrode material and lithiated superfoldable negative electrode material; Second, take the lithiated superfoldable positive electrode material as a self-supporting positive electrode, take the lithiated superfoldable negative electrode material as a self-supporting negative electrode, and select a Celgard series separator (microporous single-layer or multi-layer membrane whose main component is polypropylene or a mixture of polypropylene and polyethylene) as the porous separator. The battery consists of a separator, a lithium salt organic electrolyte, an insulating polymer membrane as the outer encapsulation material, and ultra-thin aluminum foil and copper foil as positive and negative electrodes, respectively. The layers are stacked to form a full battery. The porous separator includes any one or more of the following: Celgard series separators (microporous single-layer or multi-layer membranes whose main components are polypropylene or a mixture of polypropylene and polyethylene), thin-layer glass fiber, and paper separators. The electrodes are connected to the self-supporting positive and negative electrodes by bonding them with a mixture of PVDF adhesive and carbon nanotubes (PVDF: N-methylpyrrolidone: CNTs = 1:19:5wt%).
[0015] The role and effect of invention
[0016] According to embodiments of the present invention, a superfoldable lithium-ion battery electrode material, its preparation method, and a superfoldable full battery are provided. The preparation method of the superfoldable lithium-ion battery electrode material involves first dispersing carbon nanotubes and LiFePO4 particles in an N,N-dimethylformamide solution, followed by ultrasonication and stirring to obtain a uniform suspension. Then, polyacrylonitrile is added to the suspension, and stirring promotes the dissolution of polypropylene to obtain a polymeric mixed gel. The polymeric mixed gel is then loaded into a syringe for electrospinning to prepare a polymeric membrane precursor. The polymeric membrane precursor is then pre-carbonized in a tube furnace to obtain a pre-carbonized sample. Finally, the pre-carbonized sample is carbonized to obtain the superfoldable lithium-ion battery electrode material.
[0017] Therefore, the superfold full cell made from the superfold lithium-ion battery electrode material prepared therein can not only avoid structural damage during 500,000 folding cycles, but also maintain stable and excellent electrochemical performance.
[0018] Furthermore, the preparation method of this superfoldable lithium-ion battery electrode material is simple and efficient, which is conducive to large-scale production and has broad application prospects in the field of flexible devices.
[0019] In addition, since the superfoldable full battery provided by the present invention includes a superfoldable battery electrode material prepared by the preparation method of the superfoldable lithium-ion battery electrode material of the present invention, the superfoldable full battery can also maintain its structure without damage during multiple folding processes, while its electrochemical performance can remain stable. Attached Figure Description
[0020] Figure 1 The XRD and SEM images of the self-supporting superfoldable cathode material in Example 2 are shown.
[0021] Figure 2 The XRD and SEM images of the superfoldable anode material obtained in Example 2 are shown.
[0022] Figure 3 The resistivity change graph and crease SEM image of the superfoldable cathode material obtained in Example 2 after 500,000 folds are shown.
[0023] Figure 4 SEM images of the non-hyperfolded lithium-ion electrode material obtained in Example 4 after being folded several times are shown.
[0024] Figure 5 A digital photograph of another non-hyperfolded lithium-ion electrode material obtained in Example 5 after several folds is shown.
[0025] Figure 6 The digital graphs of the unfolding / folding test of the superfoldable full cell obtained in Example 6 during multiple folding processes and the in-situ dynamic folding electrochemical test performance are shown. Detailed Implementation
[0026] To make the technical means, creative features, objectives and effects of the present invention easy to understand, the following embodiments, in conjunction with the accompanying drawings, specifically illustrate a superfoldable lithium-ion battery electrode material, its preparation method, and the superfoldable full battery of the present invention.
[0027] Example 1
[0028] This embodiment provides a superfoldable lithium-ion battery electrode material and its preparation method.
[0029] The electrode materials for superfolded lithium-ion batteries can be either superfolded positive electrode materials or superfolded negative electrode materials, and the preparation processes for the two are slightly different.
[0030] The preparation method of superfoldable cathode material includes the following steps:
[0031] Step 1: Disperse 0.4g of carbon nanotubes and 0.1g of LiFePO4 particles in 10mL of N,N-dimethylformamide solution, sonicate for 1h and stir magnetically for 2h to obtain a suspension.
[0032] Step 2: Dissolve 1.3g of polyacrylonitrile in the suspension obtained in Step 1, and stir magnetically for 6 hours to obtain a polymer mixed gel.
[0033] Step 3: Load the polymer mixed gel obtained in Step 2 into a syringe, set the voltage at the syringe needle connection end to 12kV, the voltage at the spinning product receiving end to -2kV, the advance speed to 0.01mL / min, the receiving distance to 18cm, and the needle advance volume to 2mL / h, and perform electrospinning to prepare the polymer membrane precursor.
[0034] Step four involves pre-carbonizing the polymer composite film precursor prepared in step three. Specifically, the temperature is increased to 260°C in air at a rate of 1°C / min, then held at 260°C for 2 hours, and finally cooled to room temperature. Then, a carbonization process is performed: the temperature is increased to 260°C in a nitrogen atmosphere at a rate of 2°C / min and held for 1 hour, then increased to 700°C at a rate of 1°C / min and held for 2 hours to obtain the superfolded cathode material.
[0035] The preparation method of the superfolded anode material is exactly the same as steps one to four of the preparation method of the superfolded cathode material described above, except that the reaction conditions in step five are slightly different. Specifically, step five of the preparation method of the superfolded anode material is as follows:
[0036] Step 5: The polymer composite membrane precursor prepared in Step 3 is first subjected to pre-carbonization treatment. Specifically, it is heated to 260°C in air at a heating rate of 1°C / min, then held at 260°C for 2 hours, and then cooled to room temperature. Then, carbonization treatment is performed, specifically, it is heated to 260°C in a nitrogen atmosphere at a heating rate of 2°C / min and held for 1 hour, then heated to 800°C at a heating rate of 1°C / min and held for 2 hours to obtain the superfolded anode material.
[0037] Example 2
[0038] This embodiment provides a superfoldable lithium-ion battery electrode material and its preparation method.
[0039] The electrode materials for superfolded lithium-ion batteries can be either superfolded positive electrode materials or superfolded negative electrode materials, and the preparation processes for the two are slightly different.
[0040] The preparation method of superfoldable cathode material includes the following steps:
[0041] Step 1: Disperse 0.5g of carbon nanotubes and 0.2g of LiFePO4 particles in 10mL of N,N-dimethylformamide solution, sonicate for 1h and stir magnetically for 2h to obtain a suspension.
[0042] Step 2: Dissolve 1.3g of polyacrylonitrile in the suspension obtained in Step 1, and stir magnetically for 8 hours to obtain a polymer mixed gel.
[0043] Step 3: Load the polymer mixed gel obtained in Step 2 into a syringe, set the voltage at the syringe needle connection end to 12kV, the voltage at the spinning product receiving end to -2kV, the advance speed to 0.01mL / min, the receiving distance to 18cm, and the needle advance volume to 2mL / h, and perform electrospinning to prepare the polymer membrane precursor.
[0044] Step four involves pre-carbonizing the polymer composite film precursor prepared in step three. Specifically, the temperature is increased to 260°C in air at a rate of 1°C / min, then held at 260°C for 2 hours, and finally cooled to room temperature. Then, a carbonization process is performed: the temperature is increased to 260°C in a nitrogen atmosphere at a rate of 2°C / min and held for 1 hour, then increased to 700°C at a rate of 1°C / min and held for 2 hours to obtain the superfolded cathode material.
[0045] Figure 1 The XRD and SEM images of the superfolded fiber cathode material obtained in Example 2 are shown.
[0046] Depend on Figure 1 As seen in the XRD pattern, this composite material is composed of three substances: PAN-derived amorphous carbon, carbon nanotubes, and LiFePO4. Figure 1 As can be seen from the SEM images, the composite material is mainly composed of a mesh structure assembled by interlocking and dispersing fibers, with LiFePO4 and carbon nanotubes mainly encapsulated inside the fibers.
[0047] The preparation method of the superfolded anode material is exactly the same as steps one to four of the preparation method of the superfolded cathode material described above, except that the reaction conditions in step five are slightly different. Specifically, step five of the preparation method of the superfolded anode material is as follows:
[0048] Step 5: The polymer composite membrane precursor prepared in Step 3 is first subjected to pre-carbonization treatment. Specifically, it is heated to 260°C in air at a heating rate of 1°C / min, then held at 260°C for 2 hours, and then cooled to room temperature. Then, carbonization treatment is performed, specifically, it is heated to 260°C in a nitrogen atmosphere at a heating rate of 2°C / min and held for 1 hour, then heated to 800°C at a heating rate of 1°C / min and held for 2 hours to obtain the superfolded anode material.
[0049] Figure 2 The XRD and SEM images of the superfolded fiber cathode material obtained in Example 2 are shown.
[0050] Depend on Figure 2 As seen in the XRD pattern, this composite material consists of four substances: PAN-derived amorphous carbon, CNTs, Li3PO4, and Fe2P. The LiFePO4 phase has been almost completely decomposed. Figure 2 As can be seen from the SEM image, the negative electrode material is also mainly composed of a mesh structure assembled by interlocking fibers that are dispersed from each other, and the fibers still appear intact without any breaks.
[0051] Figure 3 The resistivity change graph and crease SEM image of the superfolded fiber cathode material obtained in Example 2 after 500,000 folds are shown.
[0052] Depend on Figure 3 As can be seen from the resistivity variation diagram, the fiber membrane can maintain a relatively stable resistivity during folding. Figure 3 The SEM image of the crease shows that the fiber membrane is intact overall, with two distinct grooves at the crease. The fibers at the grooves remain intact, without any signs of breakage.
[0053] Example 3
[0054] This embodiment provides a superfoldable lithium-ion battery electrode material and its preparation method.
[0055] The electrode materials for superfolded lithium-ion batteries can be either superfolded positive electrode materials or superfolded negative electrode materials, and the preparation processes for the two are slightly different.
[0056] The preparation method of superfoldable cathode material includes the following steps:
[0057] Step 1: Disperse 0.6g of carbon nanotubes and 0.3g of LiFePO4 particles in 10mL of N,N-dimethylformamide solution, sonicate for 2h and stir magnetically for 4h to obtain a suspension.
[0058] Step 2: Dissolve 1.3g of polyacrylonitrile in the suspension obtained in Step 1, and stir magnetically for 12 hours to obtain a polymer mixed gel.
[0059] Step 3: Load the polymer mixed gel obtained in Step 2 into a syringe, set the voltage at the syringe needle connection end to 12kV, the voltage at the spinning product receiving end to -2kV, the advance speed to 0.01mL / min, the receiving distance to 18cm, and the needle advance volume to 2mL / h, and perform electrospinning to prepare the polymer membrane precursor.
[0060] Step four involves pre-carbonizing the polymer composite film precursor prepared in step three. Specifically, the temperature is increased to 260°C in air at a rate of 1°C / min, then held at 260°C for 2 hours, and finally cooled to room temperature. Then, a carbonization process is performed: the temperature is increased to 260°C in a nitrogen atmosphere at a rate of 2°C / min and held for 1 hour, then increased to 700°C at a rate of 1°C / min and held for 2 hours to obtain the superfolded cathode material.
[0061] The preparation method of the superfolded anode material is exactly the same as steps one to four of the preparation method of the superfolded cathode material described above, except that the reaction conditions in step five are slightly different. Specifically, step five of the preparation method of the superfolded anode material is as follows:
[0062] Step 5: The polymer composite membrane precursor prepared in Step 3 is first subjected to pre-carbonization treatment. Specifically, it is heated to 260°C in air at a heating rate of 1°C / min, then held at 260°C for 2 hours, and then cooled to room temperature. Then, carbonization treatment is performed, specifically, it is heated to 260°C in a nitrogen atmosphere at a heating rate of 2°C / min and held for 1 hour, then heated to 800°C at a heating rate of 1°C / min and held for 2 hours to obtain the superfolded anode material.
[0063] Example 4
[0064] This embodiment provides a non-hyperfolded lithium-ion battery electrode material and its preparation method.
[0065] The preparation method of non-hyperfolded lithium-ion battery electrode materials includes the following steps:
[0066] Step 1: Disperse 0.1g of carbon nanotubes and 0.3g of LiFePO4 particles in 5mL of N,N-dimethylformamide solution, sonicate for 3h and stir magnetically for 2h to obtain a suspension.
[0067] Step 2: Dissolve 1.6g of polyacrylonitrile in the suspension obtained in Step 1, and stir magnetically for 24h to obtain a polymer mixed gel.
[0068] Step 3: Load the polymer mixed gel obtained in Step 2 into a syringe, set the voltage at the syringe needle connection end to 16kV, the voltage at the spinning product receiving end to -2kV, the advance speed to 0.02mL / min, the receiving distance to 18cm, and the needle advance volume to 2mL / h, and perform electrospinning to prepare the polymer membrane precursor.
[0069] Step four involves pre-carbonizing the polymer composite film precursor prepared in step three. Specifically, the temperature is increased to 260°C in air at a rate of 1°C / min, then held at 260°C for 2 hours, and finally cooled to room temperature. Then, a carbonization process is performed: the temperature is increased to 260°C in a nitrogen atmosphere at a rate of 2°C / min and held for 1 hour, followed by increasing the temperature to 700°C at a rate of 1°C / min and holding for 2 hours, yielding the lithium-ion battery electrode material.
[0070] Figure 4 The SEM images of the non-hyperfolded lithium-ion electrode material obtained in Example 4 after being folded several times are shown.
[0071] The image shows obvious fiber breakage at the fold.
[0072] Example 5
[0073] This embodiment provides another non-hyperfolded lithium-ion battery electrode material and its preparation method.
[0074] The preparation method of non-hyperfolded lithium-ion battery electrode materials includes the following steps:
[0075] Step 1: Disperse 0.7g of carbon nanotubes and 0.6g of LiFePO4 particles in 10mL of N,N-dimethylformamide solution, sonicate for 2h and stir magnetically for 3h to obtain a suspension.
[0076] Step 2: Dissolve 1.0g of polyacrylonitrile in the suspension obtained in Step 1, and stir magnetically for 48h to obtain a polymer mixed gel.
[0077] Step 3: Load the polymer mixed gel obtained in Step 2 into a syringe, set the voltage at the syringe needle connection end to 12kV, the voltage at the spinning product receiving end to -2kV, the advance speed to 0.01mL / min, the receiving distance to 18cm, and the needle advance volume to 2mL / h, and perform electrospinning to prepare the polymer membrane precursor.
[0078] Step four involves pre-carbonizing the polymer composite film precursor prepared in step three. Specifically, the temperature is increased to 300°C in air at a rate of 5°C / min, then held at 300°C for 2 hours, and finally cooled to room temperature. Then, a carbonization process is performed: the temperature is increased to 300°C in a nitrogen atmosphere at a rate of 5°C / min and held for 1 hour, then increased to 700°C at a rate of 1°C / min and held for 2 hours to obtain the non-superfoldable lithium-ion battery electrode material.
[0079] Figure 5 A digital photograph is shown of another non-hyperfolded lithium-ion electrode material obtained in Example 5 after several folds.
[0080] It is evident that after being folded, the originally intact fiber membrane broke into two halves.
[0081] Example 6
[0082] This embodiment provides a method for preparing a superfolded full cell comprising the superfolded cathode material and the superfolded anode material prepared in any one of the embodiments 1-3, including the following steps:
[0083] Step 1: Take two pieces each of the superfolded positive electrode material and superfolded negative electrode material prepared in any one of Examples 1-3, and immerse them in a 1% lithium naphthalene solution for pre-lithiation treatment.
[0084] Step 2: Take the lithiated superfolded positive electrode material from Step 1 as the self-supporting positive electrode, the lithiated superfolded negative electrode material as the self-supporting negative electrode, the Celgard series separator (microporous single-layer or multi-layer membrane whose main components are polypropylene or a mixture of polypropylene and polyethylene) as the porous separator, the lithium salt organic system as the electrolyte, the insulating polymer membrane as the outer encapsulation material, and the ultrathin aluminum foil and copper foil as the positive and negative electrode tabs, respectively, and stack them to assemble a full cell.
[0085] Figure 6 The digital graphs of the unfolding / folding test of the superfoldable full cell obtained in Example 6 during multiple folding processes and the in-situ dynamic folding electrochemical test performance are shown.
[0086] like Figure 6 The digital photos show the unfolded and folded states of the full battery during multiple folding processes, indicating that the battery did not break during these processes. The full battery exhibited normal charge-discharge behavior and maintained a relatively stable specific capacity (1Ag) after 500,000 dynamic folding cycles. -1 Its capacity at current density is approximately 117 mAh g. -1 This demonstrates that the full cell exhibits excellent folded electrochemical stability.
[0087] Those skilled in the art should understand that this invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the invention. Various changes and modifications can be made to this invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the invention as claimed. The scope of protection of this invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a superfoldable lithium-ion battery electrode material, characterized in that, The preparation process utilizes electrospinning combined with gradient temperature carbonization technology, specifically including the following steps: S10, carbon nanotubes and LiFePO4 particles are dispersed in an N,N-dimethylformamide solution, and the mixture is ultrasonicated and stirred sequentially to obtain a suspension. The amount of N,N-dimethylformamide solution is 5-10 mL, the amount of carbon nanotubes is 0.01-0.7 g, the size of LiFePO4 particles is 10 nm-300 nm, the amount of LiFePO4 is 0.01-0.6 g, the ultrasonication time is 1 h-8 h, and the stirring time is 1 h-8 h. S20, add polyacrylonitrile to the suspension, and promote the dissolution of polyacrylonitrile by stirring to obtain a polymer mixed gel. The amount of polyacrylonitrile is 1.0-1.6g, and the stirring time is 6h-48h. S30, the polymer mixed gel is loaded into a syringe for electrospinning to prepare a polymer membrane precursor. The conditions for electrospinning are as follows: the voltage at the syringe needle connection end is set to 12-16kV, the voltage at the spinning product receiving end is set to -2kV, the advance speed is set to 0.01-0.02mL / min, the receiving distance is set to 18cm, and the needle advance volume is 2mL / h. S40, the polymer membrane precursor is pre-carbonized in a tube furnace to obtain a pre-carbonized sample. The pre-carbonization process is as follows: the temperature is raised to 250-300℃ in air at a heating rate of 0.5-5℃ / min, and held at 250-300℃ for 2 hours. After the process, the temperature is naturally cooled to room temperature. S50, the pre-carbonized sample is subjected to carbonization treatment to obtain a superfoldable lithium-ion battery electrode material. When the superfoldable lithium-ion battery electrode material is a superfoldable positive electrode material, the carbonization process in step S50 is as follows: under a nitrogen atmosphere, the temperature is raised to 250-300℃ at a heating rate of 2-5℃ / min and held for 1 hour; subsequently, the temperature is raised to 650-750℃ at a heating rate of 0.5-1.5℃ / min and held for 2 hours. When the superfoldable lithium-ion battery electrode material is a superfoldable negative electrode material, the carbonization process in step S50 is as follows: under a nitrogen atmosphere, the temperature is raised to 250-300℃ at a heating rate of 2-5℃ / min and held for 1 hour, then raised to 760-850℃ at a heating rate of 0.5-1.5℃ / min and held for 2 hours.
2. A superfoldable lithium-ion battery electrode material, characterized in that: It is prepared using the preparation method of the superfolded lithium-ion battery electrode material according to claim 1.
3. A superfoldable full battery, characterized in that: It contains the superfoldable lithium-ion battery electrode material as described in claim 2.
4. A superfoldable full battery, characterized in that, include: The superfoldable cathode material is prepared by the preparation method of the superfoldable lithium-ion battery electrode material as described in claim 1. and The superfoldable anode material is prepared by the method for preparing the superfoldable lithium-ion battery electrode material as described in claim 1.
5. The superfoldable full battery according to claim 4, characterized in that, The method for preparing the superfoldable full cell includes the following steps: The first step is to take two pieces of the superfolded positive electrode material and two pieces of the superfolded negative electrode material, immerse them in a 1% lithium naphthalene solution, and perform pre-lithiation treatment to obtain the lithiation-treated superfolded positive electrode material and the lithiation-treated superfolded negative electrode material. The second step involves using the lithium-lithiated superfolded cathode material as a self-supporting cathode and the lithium-lithiated superfolded anode material as a self-supporting anode. A Celgard series separator is selected as the porous separator, a lithium salt organic system as the electrolyte, an insulating polymer film as the outer encapsulation material, and ultra-thin aluminum foil and copper foil as the positive and negative electrode tabs, respectively. These layers are then stacked and assembled into a full battery. The connection between the electrode tab and the self-supporting positive electrode and the self-supporting negative electrode is achieved by bonding carbon nanotubes with a configured PVDF adhesive.
Citation Information
Patent Citations
Method for preparing cathode material of lithium iron phosphate without coating of pole piece
CN103236544A
Lithium pre-doping method for electrode plate of lithium-ion battery
CN105489841A
Electrostatic spinning-carbonization preparation method of foldable flexible pure nanometer carbon fiber
CN107083584A
Bendable, creasable, and printable batteries with enhanced safety and high temperture stability - methods of fabrication, and methods of using the same
US20170373284A1
